Footrest Design in Achieving an Ergonomic Sitting Posture - Anis Rohmana Malik; Tito Bisma May Wilis; Novita Lizza Anggraini; Athaya Nur Khayyirah; Archangela Adelina; Yifrans Sastra Wiguna (Universitas Islam Raden Rahmat, Malang, 2025)
Ergonomic problems, particularly postural disorders resulting from prolonged sitting, are prevalent among workers involved in administrative tasks, computer operations, and public communication activities. Extended sitting durations can cause physical fatigue, impaired blood circulation, and discomfort in the lower back and legs, which may eventually lead to decreased work efficiency and musculoskeletal complaints. This study aims to develop an ergonomic footrest equipped with adjustable features based on users’ anthropometric dimensions to improve comfort and prevent postural strain. Data were collected from 60 office workers, including measurements of sitting height, lower leg length, foot width, and other dimensions related to foot positioning while seated, using standard anthropometric instruments such as an anthropometer, measuring tape, and caliper. Data adequacy and uniformity tests were performed to ensure reliability and consistency, and percentile analysis was applied as a basis for design parameters. The final design resulted in a footrest height of 51.85 cm derived from sitting popliteal height, accommodating 95% of users for optimal posture; a width of 30 cm based on sitting popliteal width; and a length of 50.99 cm based on foot length, ensuring full foot support. The proposed ergonomic footrest design is expected to minimize the risk of postural disorders, enhance user comfort, and support overall workplace health and productivity.